An investigation of work-related strain effects and coping mechanisms among South African construction professionals. Issue 4 (3rd April 2021) - Bowen, Paul; Peihua Zhang, Rita; Edwards, Peter
Abstract: Construction is a demanding work environment. Many construction professionals experience workplace stress, leading to physiological, psychological and sociological strain effects. They adopt a variety of coping mechanisms to manage these effects. A purposive sample of 36 construction professionals (architects, project managers, construction managers, civil engineers and quantity surveyors) in Cape Town, South Africa, were surveyed regarding their perceptions of workplace strain effects and stress counter measures. The Mann–Whitney and Kruskal–Wallis non-parametric tests were used for data analysis. The findings show that the highest-ranked strain effects in terms of impact were (in descending order): "frustration", "fatigue", "strain on personal relationships", "strain on professional relationships", and "anger/irritability". Male professionals identified greater fatigue and frustration effects than females; while females felt a greater lack of self-confidence. The highest-ranked coping mechanisms in terms of impact were "travel", "non-competitive sporting activity", "music", "increased caffeine intake", and "walking". Males preferred more intensive physical activities than did females. Architects experienced anxiety more frequently than other professional groups. This study confirms important strain effects experienced by construction professionals and highlights the nature and effectiveness of counter measures. Limitations of the study include its exploratory nature and small sample size. Future research should establish the associations between strain effects and coping measures, in terms of how construction organizations can better support wellbeing among their professional employees.